Water clusters: Untangling the mysteries of the liquid, one molecule at a time - Keutsch, Frank N. (The National Academy of Sciences, 2001)
Extensive terahertz laser vibration-rotation-tunneling spectra and mid-IR laser spectra have been compiled for several isotopomers of small (dimer through hexamer) water clusters. These data, in conjunction with new theoretical advances, quantify the structures, force fields, dipole moments, and hydrogen bond rearrangement dynamics in these clusters. This new information permits us to systematically untangle the intricacies associated with cooperative hydrogen bonding and promises to lead to a more complete molecular description of the liquid and solid phases of water, including an accurate universal force field.